Odzwierciedlenie doktryny eucharystycznej Kościoła katolickiego w średniowiecznej sztuce polskiej – wybrane przykłady - Turska, Halina (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
This article presents imaging of the Eucharistic doctrine of the Catholic Church in the Polish art of the Middle Ages. Selected works of art from the area of today’s Poland are analyzed, which include Eucharistic themes, such as Man of sorrows, Christ in the Mystical Wine-Press, Veil of Veronica. The article also presents the influence of variety of historical factors, such as decisions of Ecumenical Councils of the Church, the Hussite wars, or Proto-Reformation on imaging of the Eucharistic theme. The specificity and autonomy of presentations from the area of Poland, which disseminated the doctrine of the Catholic Church, is emphasized.